PENGARUH PENGGUNAAN MEDIA SOSIAL BERMUATAN INTOLERAN TERHADAP SIKAP TOLERANSI MAHASISWA PPKn UNIVERSITAS TANJUNGPURA - Herma Suriyani Sianturi; Sulistyarini Sulistyarini; Thomy Sastra Atmaja; Amrazi Zakso; Syamsuri Syamsuri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The rapid development of social media among university students has increased the potential exposure to intolerant content, while studies examining its impact on the tolerance attitudes of PPKn students still need to be strengthened, particularly within the context of socio-cultural diversity in higher education environments. This study aims to analyze the impact of exposure to intolerant content on social media on the tolerance attitudes of students in the Pancasila and Civic Education (PPKn) Study Program at Tanjungpura University. The research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, documentation, and questionnaires distributed to 100 students from diverse religious, ethnic, and cultural backgrounds. The findings reveal that the social media platforms most frequently accessed by students are Instagram, TikTok, WhatsApp, and YouTube. While using these platforms, students often encounter various forms of intolerant content, including hate speech, ethnicity, religion, race, and intergroup-based stereotypes, provocative messages, discriminatory memes, and misinformation circulating in digital spaces. Nevertheless, most students continue to demonstrate positive attitudes of tolerance despite being exposed to such content. These attitudes are reflected in their ability to respect differences, refrain from imposing their views on others, and maintain harmonious relationships with individuals from diverse backgrounds. The study concludes that social media plays a dual role: it serves as a platform for promoting values of tolerance while also functioning as a channel for the dissemination of intolerant and harmful content. Therefore, strengthening digital literacy, social media ethics education, and multicultural dialogue within the university environment is essential to enhance students’ ability to critically evaluate information and reinforce tolerant character in the digital era. ABSTRAK Perkembangan media sosial yang semakin masif di kalangan mahasiswa telah membuka peluang meningkatnya paparan konten intoleran, sementara kajian mengenai dampaknya terhadap sikap toleransi mahasiswa PPKn masih perlu diperkuat dalam konteks keberagaman sosial budaya di lingkungan perguruan tinggi. Penelitian ini bertujuan untuk menganalisis penggunaan media sosial bermuatan intoleran terhadap sikap toleransi mahasiswa Program Studi Pendidikan Pancasila dan Kewarganegaraan (PPKn) Universitas Tanjungpura. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara mendalam, dokumentasi, dan penyebaran angket kepada 100 mahasiswa yang berasal dari berbagai latar belakang agama, suku, dan budaya. Hasil penelitian menunjukkan bahwa media sosial yang paling sering diakses mahasiswa meliputi Instagram, TikTok, WhatsApp, dan YouTube. Dalam penggunaannya, mahasiswa masih menemukan berbagai konten bermuatan intoleran, seperti ujaran kebencian, stereotip berbasis SARA, provokasi, meme diskriminatif, dan hoaks yang beredar di ruang digital. Meskipun demikian, mayoritas mahasiswa tetap menunjukkan sikap toleransi yang baik setelah terpapar konten tersebut. Sikap tersebut tercermin dalam kemampuan menghargai perbedaan, tidak memaksakan kehendak kepada orang lain, serta menjaga hubungan yang harmonis dengan individu dari latar belakang yang berbeda. Penelitian ini menyimpulkan bahwa media sosial memiliki peran ganda, yaitu sebagai sarana penyebaran nilai-nilai toleransi sekaligus media yang berpotensi menyebarkan konten negatif bermuatan intoleran. Oleh karena itu, diperlukan penguatan literasi digital, pendidikan etika bermedia sosial, dan pengembangan dialog multikultural di lingkungan kampus guna meningkatkan kemampuan mahasiswa dalam menyaring informasi serta memperkuat karakter toleran di era digital.